2022
DOI: 10.3390/ijms23169066
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Impairment after Trekking at High Altitude: A Proof of Mechanisms on Redox and Metabolic Seminal Changes

Abstract: Many authors described negative but reversible effects of high-altitude hypoxic exposure on animal and human fertility in terms of sperm concentration, function, and biochemical alterations. The aim of this study was to evaluate the acute and chronic effects of high-altitude exposure on classical sperm parameters, redox status, and membrane composition in a group of travellers. Five healthy Italian males, all lowlanders not accustomed to the altitude, were evaluated after 19 days-trekking through low, moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
2
0
2
Order By: Relevance
“…The study conducted by Paciorek et al [42] reported that the production of primary products of cellular lipid oxidation (lipid hydroperoxides) was stimulated by AgNPs and subsequently transformed into secondary lipid end-products or glutathione peroxidase substrates [43]. Our study showed an increased level of 7-KCH as a consequence of uncontrolled lipid peroxidation in testicular cells and impaired redox balance [44]. The cytotoxic and pro-oxidant effects of nanoparticles disrupt steroid hormones metabolism [3,45].…”
Section: Discussionmentioning
confidence: 51%
“…The study conducted by Paciorek et al [42] reported that the production of primary products of cellular lipid oxidation (lipid hydroperoxides) was stimulated by AgNPs and subsequently transformed into secondary lipid end-products or glutathione peroxidase substrates [43]. Our study showed an increased level of 7-KCH as a consequence of uncontrolled lipid peroxidation in testicular cells and impaired redox balance [44]. The cytotoxic and pro-oxidant effects of nanoparticles disrupt steroid hormones metabolism [3,45].…”
Section: Discussionmentioning
confidence: 51%
“… 9 High-altitude environments negatively impact spermatogenesis, testis function, penile erection, and offspring production in rats, and high-altitude activities have been shown to damage reproductive parameters in men. 9 10 11 12 13 14 15 16 17 18 19 20 The reversibility of the effects of hypobaric hypoxia exposure on the male reproductive system remains controversial. Two studies in rhesus monkeys and rats showed that the sperm parameters and testis function of animals exposed to hypobaric hypoxia did not return to normal levels even long after the return to normal living conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Así mismo, el estudio realizado por Garcia-Hjarles encontró diferencias significativas en el volumen espermático de personas nativas a nivel del mar con el de nativos de altura, pero en contraste con nuestro estudio dicho estudio contó solo con 15 participantes expuestos a altura y 9 participantes a nivel del mar (15). Además, Verratti et al (31), halló en su estudio de exposición aguda a la altura en deportistas que realizan caminatas, y dicho resultado junto con el estudio realizado por Iwasaki et al (32), el cual correlacionó la formación de ROS con la calidad espermática; señalan que el volumen seminal y los niveles de especies reactivas de oxígeno presentan una correlación inversa, siendo así que la exposición a alturas elevadas lleva a una generación mayor de especies reactivas de oxígeno desencadenado por el sometimiento a hipoxia constante, radiación UV y otros estresores fisiológicos que llevan a la alteración del volumen seminal.…”
Section: Discussionunclassified
“…pág. 31 No Categoría de comparación Categoría de comparación Si 1,317 (0,001-24463,84) 0,307 (0,208-4,531) 0,390 IMC 0,966 (0,698-1,336) 0,836…”
Section: Fiebreunclassified